KNOWLEDGE AND ATTITUDE RELATIONSHIP WITH 3M PLUS MOSQUITO NEST ERADICATION ACTIONS IN SURABAYA: Systematic Review - Lusno, MFD; Farid, Muhammad Rifqo Hafidzudin (Universitas Nahdlatul Ulama Surabaya, 2023)
Dengue is a viral disease transmitted by the Aedes mosquito that causes Dengue Hemorrhagic Fever (DHF) which is a major problem in public health and has social and economic impacts. One of the key factors for the success of DHF eradication is community behavior which includes knowledge, attitudes, and actions. The purpose of this study is to conduct a systematic review by analyzing the relationship between knowledge and attitudes with the act of eradicating mosquito nests based on 7 (seven) journal articles that have been selected from the selection process measured using the quality assessment of the literature Quality Assessment Tool for Quantitative Studies from the Effective Public Health Practice Project (EPHPP) which assesses selection bias, study design, confounders, blinding, data collection methods and withdrawals and dropouts so that the quality of the reviewed journals can be seen. The quality assessment of the journal resulted in 3 points: Strong, Moderate, and Weak. The result is that most respondents are housewives. Knowledge level is good, attitude level is good, and action is good enough. There is a relationship between knowledge and action and there is a relationship between attitude and action. The recommendation is to improve the ability of housewives and improve coordination with local Jumantik. Keywords: Knowledge, Attitude, Practice, Dengue Prevention; DHF